PENGARUH PELAYANAN PENYELENGGARAAN PRAKTIK KERJA INDUSTRI TERHADAP KOMPETENSI AGRIBISNIS TANAMAN PANGAN DAN HOLTIKULTURA KELAS XII DI SMKN 63 JAKARTA - Marissa Nur Alfiani (Jurnal Tata Kelola Pendidikan, 2021)
The research background is caused phenomenon that shows the imbalance of workload in This study aims to find out 1) The service of implementing industrial work practices in the Class XII Agribusiness Crops and Horticulture Expertise Program at SMKN 63 Jakarta 2) Mastering the competence of the Class XII Agribusiness Food Crops and Horticulture students at SMKN 63 Jakarta 3) How much influence the service implementation has industrial work practices on competence in the Class XII Agribusiness Crops and Horticulture Expertise Program at SMKN 63 Jakarta. This research uses descriptive method and quantitative approach. The sampling technique used in this study is the Slovin technique, data collection using a questionnaire. The population in this study were 50 students of Class XII. The results of this study based on data processing performed with the calculation of WMS (Weight Means Score) showed the average general trend for the Service Variables for the Implementation of Industrial Work Practices and the Competency Variables for Agribusiness Food Crops and Horticulture Class XII were in the category of Strong Enough. The results of the correlation coefficient test between the X variable and Y variable obtained a positive result of 0.457 which indicates that the X variable and Y variable have a correlation. The results of the significance test show that by testing tcount ttable (3.562 1.677) then Ho is rejected and Ha is accepted. In the results of the determination test, the variable x contributes to the variable Y by 20.9%. And 79.1% is influenced by other factors not examined in this study. Next is the results of the regression test showing -148,838 + 5,918X. The conclusion of this study is that there is a positive and significant influence between the service delivery of industrial work practices on the competence of food crop agribusiness and horticulture class XII at SMKN 63 Jakarta which is classified as very good category.